BSR 2019 Annual Meeting: Program - Nicolas De Vos; Lieven Van Hoe; Martijn Grieten; Patrik Aerts (Journal of the Belgian Society of Radiology, 2019)
For the Belgian Society of Radiology (BSR) 2019 Annual Meeting, the sections on Abdominal Imaging and Leadership, Management and Quality (LMQ) and the Young Radiologist Section (YRS) joined forces to organize parallel morning sessions on pelvic imaging and LMQ. The afternoon program kicks off with a message from the BSR president followed by a session on radiation protection and a short quiz provided by the YRS.